Alexandria Smoke Eaters Can t (Tufts Archival Research Center, 2007)
Newspaper article from a 1977 Washington Post regarding a new policy developed by the Alexandria Fire Department requiring new firefighters to pledge that they will not smoke tobacco products on or off the job. Notes that it was an appropriate time for the department to issue the smoking regulation as they had been in the process of reviewing their medical standards and in the process of hiring 12 new firefighters. Mentions studies that show the on-the-job performance of firefighters that smoke fails to measure up to non-smokers.